The hungry scientist handbook : electric birthday cakes, edible origami, and other DIY projects for techies, tinkerers, and foodies /: electric birthday cakes, edible origami, and other DIY projects for techies, tinkerers, and foodies. ([2008]) - Unknown
No abstract available